2008
DOI: 10.1080/01446190802459916
|View full text |Cite
|
Sign up to set email alerts
|

Health and safety management in developing countries: a study of construction SMEs in Ghana

Abstract: Abstract:The construction industry plays a significant role in the economy of developing countries. The sector is, however, also one of the most hazardous with frequent accidents and health related problems. The purpose of this study is to examine the health and safety practices of construction small and medium-sized businesses (SMEs) in Ghana with a view to improving the health and safety performance of the sector. A survey questionnaire was administered to owner/managers of SMEs, with a response rate of 32% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
99
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 16 publications
9
99
1
4
Order By: Relevance
“…The use of questionnaires is not uncommon in construction H&S studies (cf. Langford et al, 2000;Kheni et al, 2008;Frontline Consultants, 2011) and in particular construction accident causation studies (cf. Whittington et al, 1992;Hide, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The use of questionnaires is not uncommon in construction H&S studies (cf. Langford et al, 2000;Kheni et al, 2008;Frontline Consultants, 2011) and in particular construction accident causation studies (cf. Whittington et al, 1992;Hide, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…This study adopts a tighter definition of SMEs suggested by Kheni (2008) and Kheni et al (2008) as family run domestic contractors with the following thresholds relating to medium, small and micro construction businesses:…”
Section: Definition Of Smesmentioning
confidence: 99%
“…This development has affected the construction industry as indicated by Annan et al (2015). Kheni et al (2008) identified inadequate government support for regulatory institutions and lack of skilled human resources. Dadzie (2013) also identified H&S training deficiency, inability to assess danger and workers reluctant attitudes towards H&S. Human resources development and inadequate OHS capacity for the industry has been indicated as some of the challenges (Puplampu and Quartey, 2012).…”
Section: Occupation Health and Safety Challenges In Ghanamentioning
confidence: 99%